Les démarches des sociologies francophones de l’environnement : comment faire science avec la problématique environnementale ? - Philippe Boudes (VertigO, 2006)
This article studies the constitution of the sociology of the environment as an autonomous scientific field. While relying on the history of the Québécois and French sociologies of the environment, we show that in spite of their differences, there exists common principles governing the constitution of this field. Indeed, one notices that if the environment is a sociological object, then it must be definable as an empirical and interpretable object by theories; and if sociology can study the environment, then it must propose its own analytical process for this study. We describe these analytical processes which permit, according to us, the structuration of this field, and conclude on the conceptual and theoretical reach of such a tool.